Uptake of Integrated Community Case Management and Associated Factors Among Caregivers of Children Under Five Years in Apac District, Northern Uganda - Job, Eluk; Omech, Bernard; Akello, Anne Ruth; Abeja, Christine Joy; Kambugu Nabasirye, Caroline; Auma, Anna Grace; Kumakech, Edward (Current Research in Interdisciplinary Studies, 2023)
Globally, child mortality remains a public health concern with 38 deaths per 1000 live births and accounting for 5.2 million deaths in children under 5 years, with Sub-Saharan Africa region having the highest figure of 76 deaths per 1,000 live births that is equivalent to one child in 13 dying before reaching age five in 2019. In Uganda, the child mortality rate has reduced gradually from 191 deaths per 1000 live births to 45.8 deaths per 1000 live births in 2019. Objective: To determine the Uptake of integrated community case management of childhood illnesses and associated factors among caregivers of children under five years in Apac district. Methods: This was a cross-sectional study using quantitative methods, 403 family caregivers of children under five in Apac District. Data was collected using a semi-structured questionnaire on Uptake, associated factors, and perceptions of caregivers towards ICCM services. Data was analyzed using STATA version 15.1. Results: The majority of the caregivers were female 337 (83.6%), with a mean age of 27.7 years and standard deviation of 6.64 years, attained primary education, 253(62.8%), Christians, 393 (97.5%), and married 346 (85.9%) were married. The level of Uptake of ICCM services was 38.7% (156/403). Results of the study indicate that the child’s illness (p=0.01, AOR=3.5(2.1-7.2), knowledge of ICCM (P<0.01, AOR12.1 (1.7-87), timely services (p<0.001, AOR (12.7(3.4-47), and referral by VHT (P<0.01, AOR 4.0(1.4-11.0). were statistically significant. Conclusion: The Uptake level of ICCM services provided by the VHTs was low, though caregivers had a good perception of ICCM services and child referral to health facilities by VHT. To improve Uptake of ICCM services, there is a need to provide more information regarding ICCM within the community.
Keywords: Uptake; Children under five; Childhood illnesses; Perception; ICCM; Caregivers